Cardiac involvement in adult patients with febrile thrombocytopenia diagnosed by bedside 2-D echocardiography - Gnanamuthu, Selvarani; ., Balasubramanian; S. R., Veeramani; S., Naina Mohammed; S., Sivakumar G.; S., Sathish Kumar; R., Ramesh; ., Hemanath; G., Nagasundar; M., Saravanan (International Journal of Advances in Medicine, 2018)
Background: Febrile thrombocytopenia due to various etiologies is very common in India. Its clinical manifestations range from asymptomatic infections to severe disease. Cardiac involvement in such systemic illness should be evaluated. Aim of present study is to evaluate cardiac involvement in patients with Febrile thrombocytopenia with platelets count less than 50,000/µL with the help of handheld echocardiography. Methods: Two hundred patients who had fever with thrombocytopenia were enrolled in the study. ECG and echocardiogram were done to all the patients. One-way ANOVA, Chi square test and correlation coefficient from Pearson correlation and P value of < 0.05 was taken as significant. Results: Out of 200 patients there were 146 males and 56 females. The mean age was 24.12yrs in males 28.32yrs in females .Rhythm abnormalities were present in 60 patients and the most common abnormality was sinus tachycardia; 17 patients had ascites and right pleural effusion; 24 patients presented with pericardial effusion and incidental diagnosis of CHD, RHD, and CAD were made; two patients had myocarditis as evidenced by global hypokinesia of left ventricle. All of those cardiac manifestations were common in Dengue Shock Syndrome. Conclusions: Cardiovascular manifestation in Febrile thrombocytopenia is relatively common ranging from pericarditis to myocarditis. Clinician should routinely screen patients with pyrexia with thrombocytopenia for cardiac manifestations. Early diagnosis at bed side may improve the outcome. Management of patients with pre-existing cardiac diseases should be individualized.